Rubella Immunity among Pregnant Women in a Canadian Provincial Screening Program - Mark J Kearns; Sabrina S Plitt; Bonita E Lee; Joan L Robinson (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: There are limited recent data on rubella immunity in women of childbearing age in Canada. In the present paper, the proportion of rubella seroreactivity and redundant testing (testing of women previously seropositive when tested by the same physician) in the Alberta prenatal rubella screening program were studied.